2013
DOI: 10.7235/hort.2013.13021
|View full text |Cite
|
Sign up to set email alerts
|

CMV-P1 Resistance Evaluation Using Enzyme-linked Immunosorbent Assay of Pepper Genetic Sources (Capsicum spp.)

Abstract: Abstract.Recently, Cucumber mosaic virus (CMV)-P1 infection in pepper cultivation is very serious problem, which causes low marketability and yield. In this research, 56 domestic pepper cultivars including 20 PR (Phytophthora resistance) cultivars, 31 foreign pepper lines collected from USA and 112 genetic pepper resources form RDA Genebank were used for CMV-P1 resistance evaluation. Resistance evaluation was performed at 24 days and 51 days after artificial inoculation of peppers by enzyme-linked immunosorben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Previous study identified a CMV resistance source, Likeumjo, which was later used to develop commercial varieties, such as “Bukang” ( Kang et al, 2010 ). Yao (2013) evaluated several breeding lines and accessions of C. annuum and found a resistant accession “ BJ0747-1-3-1-1 .” Screening of 199 genetic pepper resources by Shin et al (2013) resulted in the identification of 32 resistant or moderately resistant Capsicum accessions to CMV P 1 . Min et al (2014) reported three accessions, “ I7339 ,” “ ICPN-18-8 ,” and “ Daedlbo ,” with resistance to CMV P 1 .…”
Section: Pepper Genetic Resources For CMV Resistancementioning
confidence: 99%
“…Previous study identified a CMV resistance source, Likeumjo, which was later used to develop commercial varieties, such as “Bukang” ( Kang et al, 2010 ). Yao (2013) evaluated several breeding lines and accessions of C. annuum and found a resistant accession “ BJ0747-1-3-1-1 .” Screening of 199 genetic pepper resources by Shin et al (2013) resulted in the identification of 32 resistant or moderately resistant Capsicum accessions to CMV P 1 . Min et al (2014) reported three accessions, “ I7339 ,” “ ICPN-18-8 ,” and “ Daedlbo ,” with resistance to CMV P 1 .…”
Section: Pepper Genetic Resources For CMV Resistancementioning
confidence: 99%
“…Today, infection with Cucumber mosaic virus (CMV)-P1 in pepper production is a very serious issue, causing poor marketability of produce (Adama et al, 2020). Shin et al (2013) revealed that Korean domestic pepper cultivars on the market were susceptible to CMV-P1, but 17.2% of foreign pepper cultivars and genetic pepper lines from RDA Genebank were resistant or partially resistant. These findings indicate that evolved CMV strains have emerged and they can overcome the cmr1 resistant gene when experimentally inoculated through mechanical inoculation on pepper plants.…”
mentioning
confidence: 99%
“…Forty-five days post-inoculation, the cabbage lines were visually assessed for symptom severity according to a 5-point rating scale proposed by Shin et al (2013) and Ntui et al (2014) with some modifications. A modified version of the scale was adopted for the study, and the lines were categorized in a 5-degree scale as highly resistant (HR), resistant (R), moderately resistant (MR), moderately susceptible (MS), and susceptible (S) on the basis of biological assay, symptoms expression, disease rating scale, and serological tests (Shin et al 2013).…”
mentioning
confidence: 99%
“…A modified version of the scale was adopted for the study, and the lines were categorized in a 5-degree scale as highly resistant (HR), resistant (R), moderately resistant (MR), moderately susceptible (MS), and susceptible (S) on the basis of biological assay, symptoms expression, disease rating scale, and serological tests (Shin et al 2013). All plants in each line were scored; the ratings totaled and were divided by the number of plants to give a disease index for the line.…”
mentioning
confidence: 99%